Effect of fillers on the oxidative ageing of bitumen and cohesive bond strength of mastics - Rahim, Abdur (2017)
The researchers in pavement materials are always in the quest for the development of new methods and techniques to investigate the time temperature dependant behaviour of binding materials. This is paving a way for the future to build durable pavements through cost effective materials and methods. This approach by researchers to evaluate elastic, viscous and flow properties to understand complex mechanism such as ageing and moisture damage is leading to development of new methods. In this regard, the key methods for ageing includes ‘Rolling Thin Film Oven (RTFO) and ‘Pressure Ageing Vessel (PAV)’. This approach to develop new methods, despite its advantages, has natural tendency to overlook the use of the good old school testing techniques such as 'Thin Film Oven (TFO)' for its potential use for long term ageing. In the first part of this research the use of TFO for long term ageing has been explored. The research about the ‘materials’ aspect is focusing on the use of modifiers to enhance binder properties. The use of expensive modifiers such as polymers, anti-stripping agents, and adhesion promoters is not a cost-effective panacea to the problem. The use of fillers to enhance desirable properties and minimise undesirable effects can lead towards a more sustainable solution in this regard. It also has been argued that aggregate in asphalt mixture is a mastic coated particle than simply being bitumen coated. This means the mastics are closer to actual field binder particle interactions. The additional advantage of this approach towards use of filler can be advantageous to understand the role of aggregate in the mixture while remaining in the domain of ‘binder’. This can be helpful to understand the behaviour of aggregate through cost effective techniques. This research uses different filler to study two materials related mechanism. This include ageing of bitumen/mastics and their cohesive strength. The ageing aspect is studied through rheological testing and cohesive bond strength is studied through pull off type test techniques. The ageing part was further divided into two parts. The first part aimed at to evaluate the potential of the ‘Thin Film Oven’ for long term oxidative ageing as discussed earlier. The second aspect included study of the effect of the physical properties of the filler particulates on bitumen. This effect was mainly evaluated in terms of packing fraction and nature of the filler particles. The effect of fillers on the stiffening potential and long-term ageing was also evaluated using rheological testing. The work on cohesive bond strength was carried out through pull off type tests. These tests are getting popularity in research because of their ability to address most fundamental mechanical property i.e. tensile strength. Additionally, providing more detailed information about failure mode and mechanism. The integrity of the mastics was initially studied using two techniques developed in Nottingham Transportation Engineering Centre (NTEC). The variability and procedural issues in these test methods led to development of a new test method namely ‘Compression Pull Off Test Assembly’. This new test method has led to improved test procedure and helped to explain material behaviour which was not fully being captured in the previous two methods as well as in historical research methods.